2010
DOI: 10.1590/s0102-86502010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition versus enteral nutrition in severe acute pancreatitis

Abstract: Purpose:To compare the effect of parenteral versus enteral nutritional support in severe acute pancreatitis, with respect to efficacy, safety, morbidity, mortality and length of hospitalization. Methods: The study was comprised of 31 patients, divided into a parenteral group (n=16) and an enteral group (n=15), who met severity criteria for abdominal tomography (Balthazar classes C, D, and E). The patients were compared by demographics, disease etiology, antibiotic prophylaxis, use or not of somatostatin, nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…The other study performed by Vieira JP, et al revealed that, TPN was started within 48 hours of admission before 1999, but after 1999, EN was administered instead. This change was in conformity with the development of the artificial nutrition support [30]. Despite of its undeniable limitation of retrospection, the data report was detailed, clear, and precise.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…The other study performed by Vieira JP, et al revealed that, TPN was started within 48 hours of admission before 1999, but after 1999, EN was administered instead. This change was in conformity with the development of the artificial nutrition support [30]. Despite of its undeniable limitation of retrospection, the data report was detailed, clear, and precise.…”
Section: Resultssupporting
confidence: 54%
“…Later, two more studies were included: one in Chinese was found in the local science journal [20]; another one was found in the cited references of other articles [21]. At last a total of 11 articles were included and analyzed [20]–[30] (Table 1; Figure 1). Among them, nine were available as full-text paper and two were published in abstract form only [26], [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations